From Billions of Seedlings to Sustainable Livelihoods: A Critical Review of Ethiopia's Green Economy Strategy, Afforestation Outcomes, and Community Co-Benefits - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
Ethiopia's Green Legacy Initiative (GLI), launched in 2019, represents one of the most ambitious reforestation programs globally, aiming to plant 50 billion seedlings by 2026. This critical review synthesises evidence on the GLI's policy architecture, ecological outcomes, community co-benefits, and implementation challenges, drawing on peer-reviewed literature, policy documents, and empirical studies published between 2011 and 2026. The review reveals remarkable quantitative achievements: over 48 billion seedlings planted district forest cover expansion from 17.2% to 24%, soil erosion reduction from 1.9 billion to 208 million tonnes annually, and the creation of over 767,000 jobs. However, significant implementation gaps persist. Independent studies report seedling survival rates as low as 39.80% at the district level, substantially below the 85% officially reported, while 90,000–100,000 hectares of forest continue to be lost annually. Community benefits remain unevenly distributed, with smallholder farmers facing compliance challenges under international regulations such as the EU Deforestation Regulation (EUDR). Institutional weaknesses in law enforcement, data systems, land tenure, and coordination, compounded by a critical financing gap, with only 6% of the required US7.5 billion annual budget available, undermine long-term sustainability. The review concludes that transitioning from quantity-focused planting to quality-oriented ecosystem restoration, strengthening participatory governance, enhancing monitoring and evaluation systems, and scaling up private sector engagement are essential pathways forward. Ethiopia's experience offers valuable lessons for the Global South on navigating the complex terrain of environmental restoration, economic development, and social equity, demonstrating that political will and mass mobilization must be complemented by robust institutional frameworks and equitable benefit distribution to achieve lasting impact.